The rogue from within: the denial of torture in Italian prisons - Scalia, Vincenzo (Critical criminology, 2016)
In October 2009, Stefano Cucchi was beaten to death by prison guards while in custody. Italian public opinion toward prisons changed because of this event. Civil society organizations rose the level of awareness by showing how routine these abuses have become. This paper discusses the case of prisoners tortured in the prison of Asti, near Turin. Through the use of Stanley Cohen’s categories of denial, it will be shown how force relations inside prison make abuses possible.